Facial muscles reactions to other person’s facial expressions of pain - Švegžda, Algimantas; Stanikūnas, Rytis; Augustinaitė , Kristina; Bliumas, Remigijus; Vaitkevičius, Henrikas (Psichologija, 2021)
The aim of this study was to record facial electromiograms (EMG) while subjects were viewing facial expressions of different pain levels (no-pain, medium pain and very painful) and to find objective criteria for measuring pain expressed in human’s face. The study involved 18 students with age 21 years. The magnitude of the EMG response of m. corrugator supercilii depended on voluntary performed facial pain expression in the subjects. EMG responses of voluntary performed facial pain expressions to mirrored pain reactions were detected at two time span intervals: 200–300 ms after stimulation in m. zygomaticus major, and 400–500 ms after stimulation in m. corrugator supercilii. These differences disappear after 1300 ms. In the second time interval, differences in EMG responses of both muscle groups occur 1600 ms after stimulus presentation, but disappear differently: 3100 ms after stimulation in m. zygomaticus major and 4000 ms in m. corrugator supercilii. Constant responding with “medium pain” expression when recognizing faces of different pain expressions have an effect on the voluntary EMG responses of individual subjects. Images with emotional expression “no pain” reduce m. corrugator supercilii activity and increase m. zygomaticus major activity for those observers.